SHORT OVERVIEW OF ENCAPSULATION TECHNOLOGIES FOR DELIVERY OF BIOACTIVES TO FOOD - K. Trifkovic; G. Tadić; B. Bugarski (Journal of Engineering & Processing Management, 2016)
Encapsulation strategy has emerged as a mean to protect sensitive bioactive compounds, toimprove their stability and to deliver their active forms to the targeted place. A number ofbioactives can be encapsulated – cells, enzymes, vitamins, minerals, aromas and flavours, foodcolourants, antioxidants, etc. Over the years various encapsulation technologies were employedin encapsulation of bioactive compounds intended to the application in food industry. Thispaper gives a short overview of commonly used technologies for the encapsulation of foodbioactives.
Keywords: encapsulation; bioactives; food applications